General properties of the balance 2.f(O) - f(H) in electrolytic systems some detailed remarks on elemental versus core balances - Anna M Michałowska-Kaczmarczyk; Tadeusz Michałowski (Open Journal of Analytical and Bioanalytical Chemistry - Peertechz Publications, 2019)
Any electrolytic system in aqueous media is described with use of charge balance, f0 = ChB, and K elemental or core balances, fk = f(Yk) (k = 1,...,K). The balances: f1 = f(H) and f2 = f(O) are the basis to formulate the linear combination f12 = 2<span style="font-size: 8.5pt; line-height: 107%; font-family: Symbol; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;">×f2 - f1 = 2×f(O) - f(H)